Evaluation of a local government "shelter and van" intervention to improve safety and reduce alcohol-related harm - Bernadette M. Ward; Belinda O'Sullivan; Penny Buykx (BMC, 2018)
Abstract Background The entertainment precincts of cities, while contributing to local economies, need to be carefully managed to mitigate harms. Individual behaviours and government regulation have typically been the foci of interventions aimed at reducing alcohol-related harm. Little is known about how changes to the built environment might influence alcohol-related harms in these settings. The aim of this study was to explore how a public shelter and a volunteer-funded and staffed mobile van in a regional city influenced perceptions of safety and reduction in alcohol-related harm. Methods An intrinsic case-study approach was used. Document reviews, qualitative interviews with 16 key informants (volunteers, licensees, police, local business owners, patrons, community members and security guards), observation, and secondary data analysis were conducted in 2016. A conceptual framework of the causative pathways linking the drivers of alcohol consumption with social and health outcomes was used to inform the analysis. Results The shelter and van were frequently utilised but there was no significant association with a reduction in the proportion of alcohol-related hospital emergency department presentations or police incident reports. Occupational health and safety risks were identified for the volunteers which had no management plan. Conclusions The findings highlight the challenge faced by local governments/authorities wanting to provide community-based interventions to complement other evidence-based approaches to reduce alcohol-related harm. Local governments/authorities with restricted regulatory oversight need to collaborate with key agencies for targeted upstream and evidence-based alcohol prevention and management interventions before investing resources. Such approaches are critical for improving community safety as well as health and social outcomes in communities at greatest risk of alcohol-related harm.